A survey on the susceptibiliy to theileria annulata infection of buffalo - Nazir DUMANLI (Eurasian Journal of Veterinary Sciences)
In this study 3 splenectomized calves, 2 splenectomized young buffalo calves aged 6 to 8 months were used. Unfed larvae of Hyalomma excavatum, which were fed on rabbit in the Parasitology Laboratory for six generations, were fed on a calf infecdet with Theileria annulata. Infected nymphs developing from these larvae were fed on a calf and a young buffalo calf. Theileria annulata infection occured in the calf but not in the young buffalo calf.